Akuntabilitas Penatausahaan, Pelaporan Dan Pertanggungjawaban Dana Desa: - Rahmadia Pratiwi; Nurzi Sebrina; Mia Angelina Setiawan (Universitas Negeri Padang, 2019)
This study discusses how to apply the principles of administrative accountability, reporting and accountability of village funds in four villages in the northern sub-district of Pariaman, Pariaman city. This study used descriptive qualitative method. Data collection techniques are carried out by observation, interviews and documentation. The results of the study show: (1) the administration is carried out by the village treasurer in the form of income, expenditure and expenditure. Receipt of delay in receiving funds from the central government. Village expenditure also has several obstacles in the process of sending funds, because there are several verification systems and shopping transaction authorizations that have not been in accordance with the applicable rules. Village financing, utilization of investment capital carried out by villages related to financing is still not optimal; (2) late reporting of village funds in stages 1 and 2, this is due to late disbursement of funds so that reporting is too late; (3) Accountability of village funds has been carried out by the village government by giving village government performance to the community through media information that is easily accessible to the village community. In order for administration, reporting, and accountability of village funds to run well, regulations are issued on time. The administrative process is required to complete the verification and authorization requirements in accordance with applicable rules